The Effect of Asean Financial Services Liberalisation on Economic Growth - Abidin, Mufti Kandaga; Pratomo, Devanto Shasta (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2024)
In 1997, ASEAN agreed to liberalise the trade in financial services in the region marking its initial agreement with AFAS (ASEAN Framework Agreement in Services). In 2019, AFAS concluded the eighth round of the trade in financial services negotiations. Based on the agreement, this research aims to quantify the level of openness and investigate the connection between the openness level and and the economic growth ASEAN 5 countries. Using random effects panel data, the ASEAN financial services liberalisation positively and significantly affects economic growth. The results confirm that liberalisation is on track. Learning from the European Union’s experience in financial services integration, this research suggests that strengthening cross-border regulation and supervision is essential for moving forward after liberalisation.